Insight into the interdependence of Ni and Al in bifunctional Ni/ZSM-5 catalysts at the nanoscale. Issue 10 (28th April 2022) - Vu, Hue-Tong; Arčon, Iztok; Souza, Danilo Oliveira de; Pollastri, Simone; Dražić, Goran; Volavšek, Janez; Mali, Gregor; Zabukovec Logar, Nataša; Novak Tušar, Nataša
Abstract : A systematic structural study of Ni in the Ni/ZSM-5 materials is presented, which is beneficial for any further investigation of the catalytic activities of Ni/ZSM-5 and other metal-modified bifunctional catalysts. Abstract : Catalyst design is crucial for improving catalytic activity and product selectivity. In a bifunctional Ni/ZSM-5 zeolite type catalyst, catalytic properties are usually tuned via varying Al and Ni contents. While changes in acid properties associated with Al sites are usually closely investigated, Ni phases, however, receive inadequate attention. Herein, we present a systematic structural study of Ni in the Ni/ZSM-5 materials by using Ni K-edge XANES and EXAFS analyses, complemented by XRD and TEM, to resolve the changes in the local environment of Ni species induced by the different Al contents of the parent ZSM-5 prepared by a "green", template free technique. Ni species in Ni/ZSM-5 exist as NiO crystals (3–50 nm) and as charge compensating Ni 2+ cations. The Ni K-edge XANES and EXAFS results enabled the quantification of Ni-containing species. At a low Al to Si ratio ( n Al / n Si ≤ 0.04), the NiO nanoparticles predominate in the samples and account for over 65% of Ni phases. However, NiO is outnumbered by Ni 2+ cations attached to the zeolite framework in ZSM-5 with a high Al to Si ratio ( n Al / n Si = 0.05) due to a higher number of framework negative charges imparted by Al. The obtained results show that the number of highly reducible and active NiO crystals is strongly correlated with the framework Al sites present in ZSM-5 zeolites, which depend greatly on the synthesis conditions. Therefore, this kind of study is beneficial for any further investigation of the catalytic activities of Ni/ZSM-5 and other metal-modified bifunctional catalysts.